Immediate and Long-Term Results after Surgical Correction of Left Ventricular Aneurysm - M. M. Furman; G. U. Baltayeva; S. V. Varbanets (Ukrainian Journal of Cardiovascular Surgery, 2020)
In the majority of cases, left ventricular aneurysm is a result of a sustained transmural myocardial infarction, which leads to progressive cardiac insufficiency. The overriding priority of a surgical correction is to remove the non-functional myocardium and restore the geometric configuration of the left ventricle.The aim. To analyze the immediate and long-term results after surgical correction of left ventricular aneurysm.Materials and methods. Within the period from 2012 till 2017 at the Ukrainian Children`s Cardiac Center, 88 patients with left ventricular aneurysm were operated. However, we were able to assess long-term outcomes in 71 (80.1%) patients, due to the inaccessibility of patients owing to the difficult geopolitical situation in the country. Depending on the method of surgical correction, two groups were formed: group A (Dor procedure) comprising 17 patients, group B (linear repair) including 71 patients. In group A (n = 17), the vast majority of patients were male (n = 16, 94.1%) vs. only 1 female patient (5.9%). A similar trend was observed in group B: there were 56 male (78.9%) and 15 (21.1%) female patients. The following parameters were considered during the echocardiographic examination: left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDD), left ventricular end-diastolic index (LVEDI), left ventricular endsystolic volume (LVESV), left ventricular end-systolic index (LVESI), localization of the aneurysm and its prevalence.Results and discussion. During the clinical and instrumental examination, ischemic cardiomyopathy was diagnosed in 6 (35.3%) patients of group A and in 8 (11.3%) patients of group B. Long-term mortality was higher in group B (n = 10, 17.2%) than in group A (n = 1, 7.7%).Conclusion. According to our study, long-term mortality was 7.7% in group A and 17.2% in group B. The factors that could influence the results were higher Euroscore II and incorrectly chosen tactics for patients with extensive akinesis of the walls of the heart in group B. We deem appropriate to perform cardiac MRI in all patients with left ventricular aneurysm at the stage of diagnosis in order to develop clear plan for surgical tactics.